Milnesium guanyinensis sp. nov. (Eutardigrada: Apochela) from Yunnan, China - Yuan, Zhimin; Liu, Qiuju; Wang, Yan; Liu, Lijie; Chen, Yan; Li, Xiaochen (Zootaxa, 2023)
A new species from China, Milnesium guanyinensis sp. nov. (Tardigrada: Eutardigrada: Apochela: Milnesiidae), is described by means of classical taxonomic analysis, i.e. morphology-based evidence, specifically obtained from light and scanning electron microscopy imaging. The new Milnesium species is characterised by the reticulated dorsal cuticle and a claw configuration [2-2]-[2-2] in hatchlings and [2-3]-[3-2] in juvenile and adult specimens. Milnesium guanyinensis sp. nov. is most similar to M. katarzynae Kaczmarek et al. 2004 and M. pacificum Sugiura et al. 2020, but it differs from them mainly by details of the dorsal sculpture and some morphometric characters. So far, there have been nearly 200 Tardigrada species reported for China, and the discovery of the new species raises the number of first known tardigrade species of the genus Milnesium in China to three.